Application of the virtual population model in the bio-economic model of long-term dynamics for exploited population of commercial invertebrates - Kirill A. Kayzer (Известия ТИНРО, 2014)
The virtual population analysis is used for complex tasks of bio-economic modeling of long-term dynamics for exploited population of commercial invertebrates, as blue king crab in the western Bering Sea. This method is based on the data of landings for the period exceeding the life span for the studied stock and provides guaranteed estimations of the age cohorts abundance. The assessments of the blue king crab stock dynamics are used in the economic block of the model that provides market assessment of the resource for evaluation of final cost for the manufactured goods. Two blocks of the bio-economic model allow to calculate a future income from exploitation of the resource that is necessary for planning of economical activity in fisheries industry.